ENT 530 Social Media Portfolio: Twinkle Radiance / Nur Amyra Natasya Azman - Azman, Nur Amyra Natasya (2021)
Twinkle Radiance was founded in March 2020 by the sole proprietorship, Amyra Azman. Amyra Azman has been interested in scented candles since her secondary school days and has been collecting a bunch of candles with different scents since then. This interest soon grew into an interest in making her scented wax melts and soon after, started a small business of scented wax melt in Petaling Jaya, Selangor. Now ranges over 10 scents, with a price of RM 15 for every 10 pieces of wax melt. As mentioned before, Amyra Azman is the sole owner, hence all the main roles and responsibilities are to be done by Ms. Amyra, such as Strategy and direction, Planning and Budgeting, Marketing and Communication, Finances, Product Improvement, and many more. Twinkle Radiance's vision is to be the ultimate number one choice of handcraft scented wax melt, with the mission to create a high-quality handcrafted Scented Wax Melt that will enchant your senses with a pleasant fragrance. For now, Twinkle Radiance only operates online with a Facebook page, where they post all of their marketing contents, such as teasers, products, and many more. For the future of Twinkle Radiance, Ms. Amyra Azman has been preparing to explore and try out more social media marketing and online shopping app that has been known and popular to many locals, such as Lazada and Shopee.